Reference Values of Erythrocyte Sedimentation Rate of Adult Healthy Subjects - Miao, Ge (Archives of medical research, 2002)
The purpose of this paper is to provide a scientific basic for a unified standard of the erythrocyte sedimentation rate (ESR) reference value of healthy subjects in China between the ages of 41 and 75 years. ESR reference values of healthy subjects between 41 and 75 years of age were collected according to Wintrobe methods. The relationship between these healthy subjects' ESR reference values and altitude was tested in this paper. It was found that the ESR reference value of 41- to 75-year-old healthy subjects decreases when altitude gradually increases; the relationship is quite significant. Method of mathematical univariate regression analysis was used to deduce two regression equations: Y^ 1 = 14.89−0.00273 X ± 3.52, and Y^ 2 = 23.92−0.00423 X ± 5.34. If the altitude value of a particular area of China is known, ESR reference value of healthy subjects (41–75 years) ) can be calculated by regression equations. Furthermore, in terms of altitude, China can be divided into the following three districts: Qingzang District; Central District, and Eastern District.